2014
DOI: 10.1371/journal.pone.0101246
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Epigenetic Modifications in Brachypodium distachyon Embryos during Seed Maturation and Germination

Abstract: Seed development involves a plethora of spatially and temporally synchronised genetic and epigenetic processes. Although it has been shown that epigenetic mechanisms, such as DNA methylation and chromatin remodelling, act on a large number of genes during seed development and germination, to date the global levels of histone modifications have not been studied in a tissue-specific manner in plant embryos. In this study we analysed the distribution of three epigenetic markers, i.e. H4K5ac, H3K4me2 and H3K4me1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 68 publications
1
24
0
Order By: Relevance
“…Indeed, tissues surrounding the embryo were shown to be more intensively demethylated than the embryo during seed imbibition in wheat and oilseed rape ( Lu et al , 2006 ; Meng et al , 2012 ). In addition, extensive DNA demethylation in the endosperms of Arabidopsis ( Hsieh et al , 2009 ), Oryza sativa (rice) ( Zemach et al , 2010 ), and Zea mays (maize) ( Lauria et al , 2004 ) and local histone modifications in Brachypodium distachyon embryos ( Wolny et al , 2014 ) have been reported. Interestingly, in P. ramosa seeds, PrCYP707A1 was shown to be expressed in the perisperm cells close to the micropyle a few hours after GR24 stimulation ( Lechat et al , 2012 ), suggesting a spatial distribution of epigenetic modifications during seed germination in P. ramosa , as already demonstrated in autotrophic plants.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, tissues surrounding the embryo were shown to be more intensively demethylated than the embryo during seed imbibition in wheat and oilseed rape ( Lu et al , 2006 ; Meng et al , 2012 ). In addition, extensive DNA demethylation in the endosperms of Arabidopsis ( Hsieh et al , 2009 ), Oryza sativa (rice) ( Zemach et al , 2010 ), and Zea mays (maize) ( Lauria et al , 2004 ) and local histone modifications in Brachypodium distachyon embryos ( Wolny et al , 2014 ) have been reported. Interestingly, in P. ramosa seeds, PrCYP707A1 was shown to be expressed in the perisperm cells close to the micropyle a few hours after GR24 stimulation ( Lechat et al , 2012 ), suggesting a spatial distribution of epigenetic modifications during seed germination in P. ramosa , as already demonstrated in autotrophic plants.…”
Section: Discussionmentioning
confidence: 99%
“…The methods for the determination of methylation levels in DNA can be divided into at least into six general groups: global DNA methylation, regional DNA methylation, genome-wide analysis, DNA methylation analysis by sequencing, detection of specific methylation patterns, and individual CpG analysis ( Figure 5 ). Some of these have been applied to study the process of both SE and zygotic embryogenesis ( El-Tantawy et al, 2014 ; Nic-Can and De-la-Peña, 2014 ; Wolny et al, 2014 ; Pérez et al, 2015b ); however, it is necessary to expand current strategies in order to have a more precise understanding of these important processes. For a complete analysis of all of the techniques used to study chromatin modifications, see Tost (2009) , Kovalchuk and Zemp (2010) , Tollefsbo (2011) , and Spillane and McKeown (2014) .…”
Section: Techniques To Determine Dna Methylationmentioning
confidence: 99%
“…6 The global levels of the distribution of the histone modifications of 3 epigenetic markers, i.e., H4K5ac, H3K4me2 and H3K4me1 in 'matured,' 'dry,' 'imbibed' and 'germinating' embryos of a model grass, Brachypodium distachyon (Brachypodium), were studied in a tissue and organ-specific manner. 7 Our results indicate that the abundance of these modifications differs in various organs and tissues of the 4 types of Brachypodium embryos. Embryos from matured seeds were characterized by the highest level of H4K5ac in RAM and epithelial cells of the scutellum.…”
mentioning
confidence: 63%